Risks for obesity development, features of food behavior and bio-impedansemetric parameters in adolescents - Z.R. Kocherha; I.S. Nedostup; B.M. Pavlykivska; N.M. Tereshkun; I.V. Kazimyrchuk (Zaslavsky O.Yu., 2021)
Background. The problem of obesity in adolescents has gained its medical and social relevance since the incidence of the disease is steadily increasing. The purpose of the study is to improve the effectiveness of early diagnosis and prevention of obesity in adolescents. Materials and methods. To study the risk factors for obesity, a comparative assessment of lifestyle among adolescents aged 15-17 years with obesity, overweight and physiological body weight was conducted. In adolescents of the same age with comorbid obesity (basic group), overweight and physiological body weight (two comparison groups), the types of food behavior were determined using the Dutch eating behavior questionnaire (DEBQ). Bioelectrical indicators of bio-impedancemetric analysis were studied on a Tanita apparatus (Japan). The probability of differences in mean values was determined using Student's t-test. Results. It was found that the frequency of imbalance of the food pyramid, movement disorders, sleep and rest, nervous tension, burdened heredity increased significantly among obese adolescents. Obesity was found to dominate by external type of eating behavior (57.2 %); at the excess weight - restrictive type (60 %); at physiological body weight - emotional type (40 %). Bio-impedancemetry showed that the reliable bioelectrical parameters of obesity were total fat (35.5 ± 4.5 % and 29 ± 2 % vs. 17.5 ± 2.5 %); visceral fat (17 ± 2 % and 12 ± 3 % vs. 8.5 ± 1.5 %); and metabolic age (33 ± 8 and 21.5 ± 1.5 years versus 16 ± 1 years). Conclusions. Risk factors for obesity include the imbalance of the food pyramid, movement disorders, sleep and rest, nervous tension, bad habits, burdened heredity. The predominance of external type of eating behavior in obesity, restrictive - in overweight and emotional type in adolescents with physiological body weight should be taken into account when prescribing personalized lifestyle adjustments. The most informative bioelectrical parameters of bio-impedancemetry were total fat, visceral fat, and metabolic age. Bio-impedancemetry as a non-invasive predictive method of diagnosing obesity can be recommended for widespread implementation in pediatric practice.